Front‐line staff perspectives on a caring culture in Chinese hospitals: Validation of a Chinese version of the Culture of Care Barometer. (31st May 2022) - Ying, Liying; Fitzpatrick, Joanne M.; Philippou, Julia; Zhang, Yaping; Murrells, Trevor; Rafferty, Anne Marie
Abstract: Aims: The aim of this study is to examine the psychometric properties of the Chinese version of the Culture of Care Barometer in health care organizations. Background: There is a lack of tools to gauge the caring culture in Chinese hospitals. The Culture of Care Barometer is a psychometrically sound measure for caring culture developed in Western settings. Methods: This study was guided by Sousa and Rojjanasrira's methodological approach. A total of 2365 staff were recruited from two tertiary hospitals. The Barometer was administered with the Hospital Culture Evaluation Index and Minnesota Satisfaction Questionnaire. Results: The content validity index was calculated as 0.99. The goodness‐of‐fit indices, apart from the model chi‐square, which was statistically significant, all exceeded established thresholds for adequate fit. The internal consistency was very satisfactory. Pearson's correlation indicated that the tool has good concurrent and convergent validity. Conclusions: The Barometer is a reliable and valid instrument to assess front‐line staff perspectives on a caring culture in Chinese hospitals. Implications for Nursing Management: Nursing managers can use the Barometer to gauge the caring culture in China. Tailored interventions can be designed to address specific domains, and additional support can be provided to more vulnerable departments or staff groups.